Nutrition education strategies to promote vegetable consumption in preschool children: the Veggies4myHeart project - Braga-Pontes, C (2021)
Abstract Objective: To test the efficacy of three nutrition education strategies on the intake of different vegetables in preschool children. Design: This is an experimental study conducted in four Portuguese preschools. The intervention consisted of 20-min educational sessions, once a week, for 5 weeks, with one of the following randomised educational strategies: Portuguese Food Wheel Guide (control), digital game, storybook, storybook and reward (stickers). All groups had repeated exposure to vegetables in all sessions. A pre- and post-test were conducted to determine vegetable intake, and a 6-month follow-up was realised. Setting: Preschools of Leiria district, Portugal. Participants: A sample of 162 children aged 3 to 6 years. All eligible children attending the preschools were invited to participate. Results: All interventions tested were effective in increasing vegetable consumption both in the short and medium term, without statistically significant differences, compared to the control group. Stickers were more effective in the short term than in the medium term. Conclusions: The nutritional education strategies associated with repeated exposure tested in this study were effective in promoting vegetable consumption in preschool children. The use of stickers may be a valid strategy to promote the consumption of vegetables less recognised by children.